2021
DOI: 10.3390/mi12070740
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Mesoporous Thin Films for Biotechnology

Abstract: Mesoporous materials bear great potential for biotechnological applications due to their biocompatibility and versatility. Their high surface area and pore interconnection allow the immobilization of molecules and their subsequent controlled delivery. Modifications of the mesoporous material with the addition of different chemical species, make them particularly suitable for the production of bioactive coatings. Functionalized thin films of mesoporous silica and titania can be used as scaffolds with properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Moreover, compared with the no-heat group, the mild heat treatment group showed better and earlier recovery from the wound. Therefore, it can be concluded that mild temperature can stimulate the tissue to undergo the first stage of the repair process [ 28 , 37 , 38 , 39 ]. The results also demonstrated that the drug-loaded PP film significantly impacted the dermal healing process, and this effect was improved using remote mild heating.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, compared with the no-heat group, the mild heat treatment group showed better and earlier recovery from the wound. Therefore, it can be concluded that mild temperature can stimulate the tissue to undergo the first stage of the repair process [ 28 , 37 , 38 , 39 ]. The results also demonstrated that the drug-loaded PP film significantly impacted the dermal healing process, and this effect was improved using remote mild heating.…”
Section: Resultsmentioning
confidence: 99%
“… 58 For example, antibacterial agents incorporated mesoporous titania thin films characterized by controlled drug release, high pore volume and high surface area which make them ideal drug loading site is among the promising materials which can be coated onto the medical devices. 59 Atefyekta et al reported titanium oxide-based mesoporous titania thin film loaded with the antimicrobial agents (vancomycin, gentamicin, and daptomycin) in its pore volume. The thin film is characterized by decreased biofilm attachment to its surface and tunable antibacterial loading observed to be increased with increasing pore volume; thus highly contribute to host tissue growth and reduced biomaterial associated infections.…”
Section: Nano-enabled Antimicrobial Thin Films: Classes Design Approa...mentioning
confidence: 99%
“…[ 5 ] Among other materials, modified porous support materials are suitable for high‐throughput applications due to their high specific surface area allowing high loading densities of active components. [ 6 ] Mesoporous inorganic and organic–inorganic hybrid films haveattracted growing interest due to their versatile potential in biotechnological applications, [ 7 ] electrochemical energy storage and conversion, [ 8 ] catalysis [ 9 ] as well as sensing. [ 10 ] Fabrication of mesoporous silica films is in most cases based on Evaporation‐Induced Self‐Assembly (EISA).…”
Section: Introductionmentioning
confidence: 99%